L’enseignement de la géographie - Köll, L. (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1957)
The author, formerly a teacher of geography, is now the Superior of a Seminary near Nancy, France. This address was delivered before a group of Superiors and Principals of secondary schools during a congress held at Nantes, in July 1956. He demonstrates vigorously that good geography teaching is impossible without a qualified teacher who bas mastered his subject.The first difficulty comes from the fact that the field of geography is so vast : it includes all countries the world over. Good qualifications are also desirable because geography, even if it is a separate discipline, is situated at a cross-road where many other sciences converge : geology, hydrology, history, economics, sociology, etc. The education of the geography teacher must enable him to use the conclusions of all other sciences as far as they help to understand the environmental and regional point of view which distinguishes geography.It is important that the geography teacher be aware of the psychological foundations of his teaching, for geography can develop specific intellectual habits, for instance, a sense of reality, a training in the art of observation, strictness in the art of description, and a discriminating sense of comparison between the various aspects of problems.Finally, the author maintains that a good teacher must know the documentary basis of his work and must have the essential references in hand. Of course, he should have at his disposal the necessary audio-visual equipment (maps, models, films slides, radio, television, etc.) kept in a special room.